2015
DOI: 10.1371/journal.pone.0140745
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Induces Autophagy by Targeting AR/miR-101 in Prostate Cancer Cells

Abstract: Autophagy is an evolutionarily conserved process responsible for the degradation and recycling of cytoplasmic components through autolysosomes. Targeting AR axis is a standard strategy for prostate cancer treatment; however, the role of AR in autophagic processes is still not fully understood. In the present study, we found that AR played a negative role in AR degrader celastrol-induced autophagy. Knockdown of AR in AR-positive prostate cancer cells resulted in enhanced autophagy. Ectopic expression of AR in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Deregulation of miRNAs contributes to the development of multiple cancers, including PCa. For instance, downregulation of tumor suppressor miRNAs in PCa, including miR-101, miR-126*, miR-145, miR-146a, miR-224, miR-330, miR-34a, and miR-200 family, was found to be associated with advanced clinical stage and tumor metastasis, and ectopic expression of oncogenic miR-NAs, including miR-221/-222, miR-21, miR-141, miR-18a and miR-125b, indicates a higher risk of PCa progression (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of miRNAs contributes to the development of multiple cancers, including PCa. For instance, downregulation of tumor suppressor miRNAs in PCa, including miR-101, miR-126*, miR-145, miR-146a, miR-224, miR-330, miR-34a, and miR-200 family, was found to be associated with advanced clinical stage and tumor metastasis, and ectopic expression of oncogenic miR-NAs, including miR-221/-222, miR-21, miR-141, miR-18a and miR-125b, indicates a higher risk of PCa progression (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al have also proven that miR-217 acts as a downstream effector of long non-coding RNA CRNDE in Caco-2 cells [36]. In addition, mounting evidence has revealed the inhibitory effects of miR-101 on autophagy in tumor cells [15,16]. Considering the effects of OCT on autophagy, we hypothesized that miR-101 might be a downstream effector of OCT and further explored the potential interaction between miR-101 and OCT treatments in LPS-treated Caco-2 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Autophagy in human hepatocellular carcinoma cells was repressed by miR-101 [15]. Abnormal up-regulation of miR-101 might suppress autophagy in prostate cancer cells [16]. TGF-β-activated kinase 1 (TAK1) is a MAP kinase kinase kinase which can be activated by toll-like receptors (TLRs).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small non-protein-coding sequences that consist of approximately 20-24 nucleotides and suppress target mRNA translation by post-transcriptionally binding to the 3′ untranslated region (3′UTR). Previous reports have suggested that miRNAs are involved in the regulation of a variety of physiological and pathological processes, including tumour growth, migration, and angiogenesis [14][15][16]. has been demonstrated to be downregulated in a number of malignant diseases, including bladder cancer, cervical cancer, breast cancer, prostate cancer, and hepatocellular carcinoma [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%